Effect of simulation-based training on surgical proficiency and patient outcomes: a randomised controlled clinical and educational trial - Aydın, Abdullatif; Ahmed, Kamran; Abe, Takashige; Raison, Nicholas; Van Hemelrijck, Mieke; Garmo, Hans; Ahmed, Hashim U.; Mukhtar, Furhan; Al-Jabir, Ahmed; Brunckhorst, Oliver; Shinohara, Nobuo; Zhu, Wei; et al. (European urology, 2022)
Background - It is hypothesised that simulation enhances progression along the initial phase of the surgical learning curve. - Objective - To evaluate whether residents undergoing additional simulation, compared to conventional training, are able to achieve proficiency sooner with better patient outcomes. - Design, setting, and participants - This international, multicentre, randomised controlled trial recruited 94 urology residents with experience of zero to ten procedures and no prior exposure to simulation in ureterorenoscopy, selected as an index procedure. - Intervention - Participants were randomised to simulation or conventional operating room training, as is the current standard globally, and followed for 25 procedures or over 18 mo. - Outcome measurements and statistical analysis - The number of procedures required to achieve proficiency, defined as achieving a score of ≥28 on the Objective Structured Assessment of Technical Skill (OSATS) scale over three consecutive operations, was measured. Surgical complications were evaluated as a key secondary outcome. This trial is registered at www.isrctn.com as ISCRTN 12260261. - Results and limitations - A total of 1140 cases were performed by 65 participants, with proficiency achieved by 21 simulation and 18 conventional participants over a median of eight and nine procedures, respectively (hazard ratio [HR] 1.41, 95% confidence interval [CI] 0.72-2.75). More participants reached proficiency in the simulation arm in flexible ureterorenoscopy, requiring a lower number of procedures (HR 0.89, 95% CI 0.39-2.02). Significant differences were observed in overall comparison of OSATS scores between the groups (mean difference 1.42, 95% CI 0.91-1.92; p < 0.001), with fewer total complications (15 vs 37; p = 0.003) and ureteric injuries (3 vs 9; p < 0.001) in the simulation group. - Conclusions - Although the number of procedures required to reach proficiency was similar, simulation-based training led to higher overall proficiency scores than for conventional training. Fewer procedures were required to achieve proficiency in the complex form of the index procedure, with fewer serious complications overall. - Patient summary - This study investigated the effect of simulation training in junior surgeons and found that it may improve performance in real operating settings and reduce surgical complications for complex procedures.
Online verfügbar 14 November 2021, Version des Artikels 15 March 2022
Gesehen am 10.03.2023